Peran Komunikasi dalam Implementasi Kebijakan Pelacakan Kontak Erat dan Pemantauan Isolasi Mandiri Penderita Covid-19 Oleh Puskesmas di Kota Palembang - Dian Hayati; Misnaniarti Misnaniarti; Haerawati Idris (Universitas Batanghari Jambi, 2021)
Carrying out close contact tracing and immediately isolating cases and contacts, is the chosen mitigation to offset the economic and social impact of the COVID-19 pandemic. This analysis of the implementation of the close contact tracing policy and monitoring of self-isolation is an important step for input from various parties to determine better policies in the future so that the pandemic can end soon. So good communication is needed between the parties involved in implementing the policy. This study is a qualitative research with a descriptive design that aims to determine the role of communication in the implementation of close contact tracing policies and self-isolation monitoring by the comunnity health centers in Palembang City 2020 which can be seen from the transmission, clarity and consistency variables using Edward III Theory. Methods of collecting data were in-depth interviews, observation and document review. The results of the study found that the lack of socialization carried out related to guidelines for prevention and contact tracing and self-isolation of COVID-19 sufferers, the ineffectiveness of socialization of guidelines carried out virtually, as well as inconsistencies in contact tracing due to several factors, firstly patient dishonesty, community stigma, data late case release, unclear address/telephone number, uncooperative patient and changes in guidelines that occurred from revision 4 to revision 5. Suggestions from this study are to evaluate the socialization of guidelines, increase knowledge and abilities of implementors, improve coordination and cooperation of implementers, empowerment of community roles so as to reduce stigma in society.